2022
DOI: 10.3390/ijms23010534
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Mesenchymal Stromal Cells Overexpressing Fas-Ligand Ameliorates Acute Graft-versus-Host Disease in Mice

Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) has the potential to cure malignant and non-malignant hematological disorders, but because of the serious side effects of this intervention its applications are limited to a restricted number of diseases. Graft-versus-host disease (GvHD) is the most frequent complication and the leading cause of mortality and morbidity following allo-HCT. It results from the attack of the transplanted T cells from the graft against the cells of the recipient. There is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A number of studies have also shown that MSCs express and secrete FasL [ 59 ]. It has been shown that FasL expression partly mediates the immunomodulatory properties of MSCs [ 60 , 61 , 62 ]. It is expected that the high expression of Fas makes these cells potentially susceptible to Fas-induced apoptosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also shown that MSCs express and secrete FasL [ 59 ]. It has been shown that FasL expression partly mediates the immunomodulatory properties of MSCs [ 60 , 61 , 62 ]. It is expected that the high expression of Fas makes these cells potentially susceptible to Fas-induced apoptosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism has been further elucidated in vitro through the transient knockdown of FasL, which revealed that activation of the Fas pathway induced MSC expression of MCP-1, promoting T lymphocyte recruitment and TGF-β expression in macrophages [74]. The transient effect of Fas-FasL pathway activation on T cells in a graft-versus-host disease (GvHD) model was improved by overexpressing FasL on MSCs in vitro and in vivo, suggesting an interesting therapeutic strategy for the treatment of GvHD [75,76].…”
Section: Mesenchymal Stromal Cells and Immunosuppressionmentioning
confidence: 99%
“…Regardless of the migration status, how MSCs prevent aGvHD in murine models remains unclear. Vacaru et al proposed a mode of action that involves the FasL pathway and showed that treatment with MSCs that overexpress FasL resulted in delayed GvHD onset and increased survival [ 119 ]. In another study, Wang Rui et al reported that MSCs derived from the umbilical cord express high levels of CXCL1, leading to the accumulation of myeloid-derived suppressor cells that control GvHD [ 120 ].…”
Section: Mscs In Mouse Models Of Gvhdmentioning
confidence: 99%